Analisis dan Desain Sistem Project Multimedia Pembelajaran pada Lembaga Kursus Sebagai Program Freedom Of Learning - Normah Normah (LPPM Universitas Bina Sarana Informatika, 2018)
Course institution is one of the educational institutions that currently not only non-formal education, but has become a need not only for school-aged children, but also for various groups of various ages. Course agencies are now competing with each other to bring quality tutors, learning materials, and complete facilities and the best. Multimedia is an option in improving the quality and quality of learning. Technology that can be applied to course institutions is only the use of website for promotion or online registration media of course participants, but in terms of learning materials can use technology, that is multimedia learning system at the institute course. Where in this multimedia project is not only available as a learning media but also can be used as a means of information, complete and widely as data center data processing data, course data, user data, Student Attendance, Value Training Exercise, and KHS students. Method, with some form of subproject, then proceed with Integration stage into one unity system.